2020
DOI: 10.1371/journal.pgen.1009016
|View full text |Cite
|
Sign up to set email alerts
|

Human ABCB1 with an ABCB11-like degenerate nucleotide binding site maintains transport activity by avoiding nucleotide occlusion

Abstract: Several ABC exporters carry a degenerate nucleotide binding site (NBS) that is unable to hydrolyze ATP at a rate sufficient for sustaining transport activity. A hallmark of a degenerate NBS is the lack of the catalytic glutamate in the Walker B motif in the nucleotide binding domain (NBD). The multidrug resistance transporter ABCB1 (P-glycoprotein) has two canonical NBSs, and mutation of the catalytic glutamate E556 in NBS1 renders ABCB1 transport-incompetent. In contrast, the closely related bile salt export … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 103 publications
(156 reference statements)
1
11
0
Order By: Relevance
“…Insertion of methionine (as present in ABCB11) in place of the Walker B glutamate of NBS1 abolished ATPase activity and substrate transport [82]. Inserting all four residues by which NBS1 of ABCB11 differs from NBS1 of ABCB1 resulted in an ABCB1 variant that can hydrolyze ATP and is substrate transport competent [82], showing that ABCB1 can in principle be active with a degenerate NBS1.…”
Section: Biochemical Evidence For Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Insertion of methionine (as present in ABCB11) in place of the Walker B glutamate of NBS1 abolished ATPase activity and substrate transport [82]. Inserting all four residues by which NBS1 of ABCB11 differs from NBS1 of ABCB1 resulted in an ABCB1 variant that can hydrolyze ATP and is substrate transport competent [82], showing that ABCB1 can in principle be active with a degenerate NBS1.…”
Section: Biochemical Evidence For Asymmetrymentioning
confidence: 99%
“…The single Walker B glutamate mutants revealed that NBS1 or NBS2 is not completely identical [41]: The verapamil stimulated ATP hydrolysis of single glutamate to glutamine mutants in NBS1 or NBS2 differed 2‐ to 3‐fold, the K m(MgATP) differed 5‐fold, while ADP is more likely retained in the Walker B mutant of NBS1 compared to NBS2. Insertion of methionine (as present in ABCB11) in place of the Walker B glutamate of NBS1 abolished ATPase activity and substrate transport [82]. Inserting all four residues by which NBS1 of ABCB11 differs from NBS1 of ABCB1 resulted in an ABCB1 variant that can hydrolyze ATP and is substrate transport competent [82], showing that ABCB1 can in principle be active with a degenerate NBS1.…”
Section: Biochemical Evidence For Asymmetrymentioning
confidence: 99%
“…Apparent affinity of nucleotide binding (K A ) was determined as described previously (Barsony et al, 2016, Goda et al, 2020. Permeabilized cells (1 × 10 6 ml − 1 ) were pre-treated with nucleotides added at different concentrations in the presence of equimolar concentrations of Mg 2+ at 37°C for 10 min and then further incubated with 5 μg/ml 5D3-A647 at 37 °C for 20 min.…”
Section: Determination Of Apparent Affinity Of Nucleotide Bindingmentioning
confidence: 99%
“…When compared to ABCB1, only four amino acids differ in NBS1. These are E502, M584, R1221 and E1223 in BSEP corresponding to S474, E556, G1178 and Q1180 in the ABCB1 protein sequence [ 71 ]. The amino acid changes result in a catalytically inactive ATP binding site (NBS1), which is also variably called “degenerate” NBS.…”
Section: Structural Models Of Bsepmentioning
confidence: 99%